KETERAMPILAN GURU DALAM MENGELOLA KELAS UNTUK ANAK BERKEBUTUHAN KHUSUS - Khobir, Khoirul; Yusuf, Muhamad; Alhusaini, Amin (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
The purpose of this study was to find out and analyze classroom management for children with special needs in SLB. The methodology used in this study is field research.Data collection techniques in this study were interviews, observation and documentation. In this study the data is analyzed by reducing data, display data and verifying the data that has been obtained. The results of this study are classroom management for children with special needs seen from the scope of the facilities and student arrangements. The arrangement of facilities at the Banyuasin State SLB is quite good, namely learning by utilizing existing facilities, utilizing nature and the surrounding environment as well as providing tools for ABK students to maximize the teaching and learning process in SLB, while for student management in Banyuasin State SLB emphasizes formation student organization, grouping of students, assignment of students, coaching and assignments, as well as report cards and class increases.